Enhancing Non English Students’ Communication Skills through Blended Learning: A Lesson from English for Specific Purposes Lens - Widiati, Bidarita; Monteoro, Cosmo Brito; Arbaiza, Barbara (Journal of Language and Literature Studies, 2024)
This study investigates the effectiveness of blended learning in enhancing English communication skills among environmental health students, focusing on oral and written competencies essential in professional contexts. The research addresses a significant gap in language education for students in specialized fields, where limited engagement and practical application opportunities in traditional settings often hinder language proficiency development. A quasi-experimental design was employed with 60 students, divided into an experimental group receiving blended learning instruction and a control group following conventional face-to-face methods. Pre- and post-test results revealed that the experimental group demonstrated a 35% improvement in overall communication skills, compared to a 10% increase in the control group. Key gains in fluency, pronunciation, sentence structure, and vocabulary usage were observed. Data from student surveys and instructor observations also indicated higher levels of motivation, engagement, and confidence in the experimental group, attributed to the blended learning model’s flexibility, multimedia resources, and immediate feedback. This study highlights the significant advantages of blended learning for language acquisition in specialized academic fields and recommends its integration into language curricula. Tailored online resources and instructor training are proposed to maximize instructional impact. By addressing the language proficiency challenges in professional education, this research offers valuable insights into effective language learning strategies and supports adopting blended learning in diverse academic disciplines.